Enhanced immunomodulatory effects of canine adipose tissue-derived mesenchymal stem cells in 3D culture - Lee, Eunbi; Lim, Ga-Hyun; An, Ju-Hyun; Ryu, Min-Ok; Seo, Kyoung-Won; Youn, Hwa-Young (Frontiers in Veterinary Science, 2025)
IntroductionMesenchymal stem cells (MSCs) have been introduced as a treatment for dogs owing to their immunomodulatory effects. In humans, 3D-cultured MSCs have recently been applied in treating various conditions, including myocardial infarction, liver disease, and kidney disease. This study aimed to evaluate whether the immunomodulatory effects of canine adipose tissue-derived MSCs (cAT-MSCs) are enhanced when cultured in a 3D environment compared to conventional 2D culture.MethodscAT-MSC spheroids were generated using ultra-low-adhesion plates. The structural and hypoxic characteristics of these spheroids were assessed via confocal imaging. The expression levels of the stemness markers SOX2 and OCT4 were examined through western blotting. Additionally, the expression of inflammatory factors within the cAT-MSC spheroids was analyzed using RT-PCR and ELISA. The immunomodulatory effects were further evaluated in canine macrophages (DH82) treated with conditioned media (CM) from cAT-MSC spheroids, using RT-PCR and flow cytometry.Results3D culture induced hypoxic conditions within the cAT-MSC spheroids and significantly increased the expression of SOX2 and OCT4 (p < 0.05). Moreover, the expression of inflammation-associated factors, including TGF-β1, TSG-6, COX-2, PGE2, and IL-10, was upregulated in the 3D culture (p < 0.05). Treatment of DH82 cells with CM from the cAT-MSC spheroids led to a significant reduction in the expression of pro-inflammatory factors such as TNF-α, IL-1β, and IL-6 (p < 0.01). Additionally, M1 polarization was diminished in DH82 cells exposed to the CM from the cAT-MSC spheroids (p < 0.0001). And M2 polarization was increased in DH82 cells exposed to the CM from the cAT-MSC spheroids (p < 0.0001).ConclusionThis study confirms that the immunomodulatory effects of MSCs are enhanced in 3D culture. Therefore, 3D cultured MSCs may offer a more effective therapeutic approach than conventional 2D-cultured MSCs for treating canine inflammatory diseases.